1982
DOI: 10.1152/jappl.1982.53.1.44
|View full text |Cite
|
Sign up to set email alerts
|

Strength of hypoxic vasoconstriction determines shunt fraction in dogs with atelectasis

Abstract: We investigated the degree to which strength of pulmonary hypoxic vasoconstriction affects perfusion of pulmonary shunt pathways in acute atelectasis. In 17 intact supine dogs (anesthetized, paralyzed, and ventilated) we produced left lower lobe atelectasis by occluding the lobar bronchus during oxygen inhalation. Subsequently, shunt fraction (reflecting perfusion of that lobe) was measured using an SF6 infusion while the dogs breathed room air; the mean was 26% (range 14-40%). Pulmonary pressor response to hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
14
0

Year Published

1985
1985
2006
2006

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 0 publications
2
14
0
Order By: Relevance
“…DISCUSSION This study demonstrates that infant animals with lobar atelectasis effectively minimize intrapulmonary shunt by reducing pulmonary blood flow to the atelectatic region. The results are similar to those reported in normal adult dogs with lobar atelec- tasis (5,6). In these previous studies, regional hypoxic pulmonary vasoconstriction was found to be the primary mechanism responsible for minimizing gas exchange abnormalities associated with lobar atelectasis (6).…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…DISCUSSION This study demonstrates that infant animals with lobar atelectasis effectively minimize intrapulmonary shunt by reducing pulmonary blood flow to the atelectatic region. The results are similar to those reported in normal adult dogs with lobar atelec- tasis (5,6). In these previous studies, regional hypoxic pulmonary vasoconstriction was found to be the primary mechanism responsible for minimizing gas exchange abnormalities associated with lobar atelectasis (6).…”
Section: Resultssupporting
confidence: 90%
“…The results are similar to those reported in normal adult dogs with lobar atelec- tasis (5,6). In these previous studies, regional hypoxic pulmonary vasoconstriction was found to be the primary mechanism responsible for minimizing gas exchange abnormalities associated with lobar atelectasis (6). The consistent rise in total pulmonary resistance in piglets following lobar collapse suggested that this mechanism of redistributing pulmonary blood flow is also operative in infant animals.…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations